PDK1 disruptors and modulators: a patent review. (May 2015) - Hossen, Muhammad Jahangir; Kim, Seung Cheol; Yang, Sungjae; Kim, Han Gyung; Jeong, Deok; Yi, Young-Su; Sung, Nak Yoon; Lee, Jeong-Oog; Kim, Jong-Hoon; Cho, Jae Youl
<x xml:space="preserve">Abstract</x> Introduction: 3-Phosphoinositide-dependent kinase 1 (PDK1) is a master regulator of the AGC protein kinase family and is a critical activator of multiple pro-survival and oncogenic protein kinases, for which it has garnered considerable interest as an oncology drug target. Areas covered: This manuscript reviews small molecule patent literature disclosures between October 2011 and September 2014 for both PDK1 activators and inhibitors and restates the selective patents published before September 2011. PDK1 modulators are organized according to pharmaceutical company and chemical structural class. Expert opinion: Many academic institutions and pharmaceutical companies continue to research into the development of small molecules that can function as PDK1 inhibitors or modulators. To date, > 50 patent publications on PDK1 disruptors and modulators have been published since the protein was first discovered in 1998. Most of these molecules act as ATP mimetics, forming similar hydrogen bonding patterns to PDK1 as ATP and functioning as hydrophobic pharmacophores. To achieve selectivity in PDK1 inhibition, the discovery of binding pockets structurally distinctive from the ATP site is a challenging but promising strategy.